Perceptions of higher education teachers about academic dishonesty in students within a virtual environment - De Fatima Uceda, Sebastiana (2022)
This study had two aims. The first aim was to identify the perceptions that higher education teachers of an education faculty, in a virtual environment, have about the factors that influence the decisions of the students to carry out dishonest academic behaviors. The second aim was to identify what measures teachers implement to prevent dishonest behaviors. Academic dishonesty is understood as the set of attitudes and actions that have the purpose of deceiving another person, and are carried out when one wants to present an academic work as one's own when in reality it is not in this way, violating the norms of the institution [1]. The present work is a qualitative research of an exploratory nature and a phenomenological approach. Semi-structured interviews were used with eight teachers. Data was analyzed: first, the concept of academic dishonesty, then the mechanism used by teachers and the institution to deal with these behaviors; finally, individual and contextual factors that may influence the student's decision to perform a dishonest behavior.